Analysis of Adolescents’ Communication Ethics Toward Parents in the Digital Era: A Study of the Sidoarjo Hilir Community, Medan Tembung District - Shifa Alya Nafisa; Mayora Chandra; Amir Khairi Armah; Zainal Abidin (Peneliti.net, 2026)
The rapid development of digital technology has significantly changed communication patterns within families, especially among teenagers. Adolescents growing up in the digital era tend to be more familiar with communication through social media and electronic devices rather than direct face-to-face interaction. This condition gradually affects teenagers’ communication ethics toward their parents, such as the use of overly casual language, lack of attention during conversations, and reduced intensity of family interactions. From the perspective of Islamic Education, ethics in speaking to parents is an important part of moral education that must be maintained under any circumstances, as explained in Surah Al-Isra verse 23 regarding the prohibition of speaking harshly to parents. This study aims to analyze teenagers’ communication ethics toward parents in the digital era within the community of Sidoarjo Hilir, Medan Tembung District, and to identify the factors influencing these changes. This study employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The research informants consisted of two teenagers and one parent selected through purposive sampling. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that digital technology has both positive and negative impacts on family communication. The positive impact can be seen in the ease of long-distance communication between children and parents. However, the study also found changes in communication ethics, such as the use of informal language toward parents, lack of focus during interaction due to smartphone use, and reduced meaningful face-to-face communication. This research also found that family roles and religious education play an important role in shaping teenagers’ communication ethics in the digital era. Therefore, strengthening moral education within the family is necessary so that technological development does not erode the values of respect toward parents.